Citrullination of C1-inhibitor as a mechanism of impaired complement regulation in rheumatoid arthritis - Martin, Myriam; Nilsson, Sara C.; Eikrem, David; Fromell, Karin; Scavenius, Carsten; Vogt, Leonie M.; Bielecka, Ewa; Potempa, Jan; Enghild, Jan J.; Nilsson, Bo; Ekdahl, Kristina N.; Kapetanovic, Meliha C.; et al. (Frontiers in Immunology, 2023)
Background: Dysregulated complement activation, increased protein citrullination and production of autoantibodies against citrullinated proteins are hallmarks of rheumatoid arthritis (RA). Citrullination is induced by immune cell-derived peptidyl-Arg deiminases (PADs), which are overactivated in the inflamed synovium. We characterized the effect of PAD2 and PAD4-induced citrullination on the ability of the plasma-derived serpin C1-inhibitor (C1-INH) to inhibit complement and contact system activation. Methods: Citrullination of C1-INH was confirmed by ELISA and Western Blot using a biotinylated phenylglyoxal probe. C1-INH mediated inhibition of complement activation was analyzed by C1-esterase activity assay. Downstream inhibition of complement was studied by C4b deposition on heat-aggregated IgGs by ELISA, using pooled normal human serum as a complement source. Inhibition of the contact system was investigated by chromogenic activity assays for factor XIIa, plasma kallikrein and factor XIa. In addition, autoantibody reactivity to native and citrullinated C1-INH was measured by ELISA in 101 RA patient samples. Results: C1-INH was efficiently citrullinated by PAD2 and PAD4. Citrullinated C1-INH was not able to bind the serine protease C1s and inhibit its activity. Citrullination of the C1-INH abrogated its ability to dissociate the C1-complex and thus inhibit complement activation. Consequently, citrullinated C1-INH had a decreased capacity to inhibit C4b deposition via the classical and lectin pathways. The inhibitory effect of C1-INH on the contact system components factor XIIa, plasma kallikrein and factor XIa was also strongly reduced by citrullination. In RA patient samples, autoantibody binding to PAD2- and PAD4-citrullinated C1-INH was detected. Significantly more binding was observed in anti-citrullinated protein antibody (ACPA) positive than in ACPA-negative samples. Conclusion: Citrullination of C1-INH by recombinant human PAD2 and PAD4 enzymes impaired its ability to inhibit the complement and contact systems in vitro. Citrullination seems to render C1-INH more immunogenic and citrullinated C1-INH might thus be an additional target of the autoantibody response observed in RA patients.